1970
DOI: 10.1136/hrt.32.6.779
|View full text |Cite
|
Sign up to set email alerts
|

Regression of valvular pulmonary stenosis.

Abstract: Eight patients with mild to moderate valvular pulmonary stenosis underwent serial physiological studies before surgical intervention. Average pulnwnary valve area at the initial study was o 59 CM.2 and at the second study (average 7-8 serial studies were performed in 8 subjects with mild to moderate valvular pulmonary stenosis to determine how valve area changes with time. These changes are related to normal pulmonary valve growth. Materials and methodsEight patients with mild to moderate valvular pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Wennevold and Jacobsen 2 observed worsening in 1 (14.2%) of 7 patients with pressure gradient < 50 mmHg. Lueker et al 12 observed a mild worsening in 1 (12.5%) of 8 patients with pressure gradient < 50 mmHg during a mean period of 7.8 years, in children. Nugent et al 9 had also noticed worsening of the pulmonary transvalvular gradient in 14% of the patients evaluated by a hemodynamic study, during a period of 4 to 8 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wennevold and Jacobsen 2 observed worsening in 1 (14.2%) of 7 patients with pressure gradient < 50 mmHg. Lueker et al 12 observed a mild worsening in 1 (12.5%) of 8 patients with pressure gradient < 50 mmHg during a mean period of 7.8 years, in children. Nugent et al 9 had also noticed worsening of the pulmonary transvalvular gradient in 14% of the patients evaluated by a hemodynamic study, during a period of 4 to 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the publications also mention a favorable evolution in pulmonary valve stenosis when they present a mild degree of severity [2][3][4][5][6][7][8][9][10][11][12][13] . Few of these 5,7 show an unfavorable evolution of the mild defect, due to the rapid worsening of the condition, similar to what is observed in more severe defects, mainly when exteriorizing occurs early in life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transpulmonary valve pressure gradient can be estimated from the peak V measured by Doppler echocardiography using a simplified Bernoulli's equation, which is, at present, regarded as the most reliable noninvasive methodology to evaluate the severity of PS (Hatle and Angelsen 1982; Lima et al 1983;Johnson et al 1984;Goldberg 1989). Although some studies on serial catheter data showed spontaneous improvement of the transpulmonary valve gradient in mild to moderate patients of PS (Leuker et al 1970;Danilowicz et al 1975), there are few noninvasive studies on the natural history of PS. In this study, to clarify the optimal age to perform not only invasive examination but also PTPV for patients with mild to moderate PS, we retrospectively surveyed the changes in peak V measured by serial Doppler echocardiography.…”
Section: Case Presentationmentioning
confidence: 99%